Design and synthesis of thiahelicenes for molecular electronics - Baciu, Bianca C.; Bronk, Pawel J.; Guijarro, Albert (Frontiers in Chemistry, 2024)
The conductance of a tunneling electron through a pi-conjugated molecule may be affected by the presence of different pathways in the orbital structure of the molecule, result of the constructive or destructive interference of the molecular wave function. This quantum interference (QI) directly translates into enhancing or suppressing conductance and offers the possibility of controlling this phenomenon through tailored synthesis. With this objective in mind, we did set up the synthetic methodologies to access to a series of thiophene-fused helicenes with a well-defined positioning of the sulfur atoms, which control the occurrence of conducting, linearly conjugated as well as disrupted, cross-conjugated pathways.We describe in this work these synthetic strategies and will relate the expected electronic transport through our molecules to three key variables: a) the exo-/endo-topology of the S atom within the ring, b) the parity (odd/even) of the overall number of rings conforming the helicene, and c) the size of the circuit. This series ranks from [7] to [11] fused rings, having both exo-, endo-or mixed exoendo-topology. Comparison of homologous dithiahelicenes with size-tunable HOMO/LUMO energies, allows us to isolate the key variable of bond topology from other electronic properties and face the study of QI in helically conjugated molecules. Understanding and tunning the conductance in this type of molecular solenoids is the main purpose of this work.